METODE HIWAR DALAM PENDIDIKAN ISLAM PERSPEKTIF AL GHAZALI - Faizin, Mohammad; Aziz, Yahya; Putri, Nurul Hanifah; Albab, Azzahra Ulil (STAI Ma'had Aly Al-Hikam Malang, 2023)
Abstract: This research aims to describe and clarify clearly how the interaction of the two components of education, namely educators and students, in the form of dialogue in Islamic education from al-Ghazali's perspective. Research results state that Islamic education is very important because it is the main reference for a person's life from birth to death. According to al-Ghazali, a child's success is determined by the strength of his or her parents and teachers. The emphasis on educators' impact on students is due to this. One of his discoveries on the educational side is the concept of educational interaction in teaching activities between educators and students; this is similar to one of the well-known Islamic educational methods, namely hiwar, or dialogue. This discussion of knowledge or education must be conducted with the full understanding that the speaker's goals include both educating and guiding his or her listener toward maturity. Keywords: Al Ghazali, islamic education, hiwar Abstrak: Riset ini ditujukan guna menguraikan dan memaparkan secara jelas interaksi dua komponen pendidikan.yakni pendidik dan anak didik berbentuk dialog dalam edukasi islam perspektif al.Ghazali. Pengerjaan riset dilakukan melalui pencarian data jadi dari penelusuran dengan media internet. Hasil riset menyatakan edukasi Islam teramat penting karena menjadi acuan utama bagi kehidupan seseorang sejak dia lahir hingga wafat. Bagi al.Ghazali, seorang anak itu tergantung atas bagaimana daya orang tua serta pengajarnya. Dimana ini menjadi penyebab penitikberatan pengaruh pendidik atas anak didik. Satu di antara yang ada atas penemuannya di sisi pendidikan ialah konsep educational interaction dalam aktivitas pengajaran antara pendidik dan anak didik, dan ini serupa dengan satu di antara sejumlah metode edukasi Islam terkenal yakni hiwar atau dialog. Dialog berisi ilmu atau edukasi ini mesti dilakukan dengan kesadaran penuh bahwa dia bermaksud mendidik juga membimbing kawan bicaranya pada maturitas. Keywords: Al Ghazali, edukasi Islam, hiwar